Bullen's Parameter as a Seismic Observable for Spin Crossovers in the Lower Mantle. Issue 18 (25th September 2017) - Valencia‐Cardona, Juan J.; Williams, Quentin; Shukla, Gaurav; Wentzcovitch, Renata M.
Abstract: Elastic anomalies produced by the spin crossover in ferropericlase have been documented by both first‐principles calculations and high pressure‐temperature experiments. The predicted signature of this spin crossover in the lower mantle is, however, subtle and difficult to geophysically observe within the mantle. Indeed, global seismic anomalies associated with spin transitions have not yet been recognized in seismologic studies of the deep mantle. A sensitive seismic parameter is needed to determine the presence and amplitude of such a spin crossover signature. The effects of spin crossovers on Bullen's parameter, η, are assessed here for a range of compositions, thermal profiles, and lateral variations in temperature within the lower mantle. Velocity anomalies associated with the spin crossover in ferropericlase span a depth range near 1, 000 km for typical mantle temperatures. Positive excursions of Bullen's parameter with a maximum amplitude of ∼0.03 are calculated to be present over a broad depth range within the middle‐to‐deep lower mantle: these are largest for peridotitic and harzburgitic compositions. These excursions are highest in amplitude for model lower mantles with large lateral thermal variations and with cold downwellings having longer lateral length‐scales relative to hot upwellings. We conclude that predicted deviations in Bullen's parameter due to the spin crossover in ferropericlase for geophysically relevant compositions may be sufficiently large to resolve in accurate seismic inversions of this parameter and could shed light on both the lateral variations in temperature at depth within the lower mantle, and the amount of ferropericlase at depth. Key Points: The Bullen's parameter perturbations due to spin crossover in fp are consistent with seismological observations and geodynamic calculations Accurate characterization of η could provide constraints on both the lateral temperature distribution and fp content at depth Inversions without spin crossover induced perturbations in η implicitly assume that no fp is present in the deep mantle